2021
DOI: 10.2903/j.efsa.2021.6593
|View full text |Cite
|
Sign up to set email alerts
|

Peer review of the pesticide risk assessment of the active substance potassium hydrogen carbonate

Abstract: The conclusions of the European Food Safety Authority (EFSA) following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member State, the Netherlands and co-rapporteur Member State, Greece, for the pesticide active substance potassium hydrogen carbonate and the considerations as regards the inclusion of the substance in Annex IV of Regulation (EC) No 396/2005 are reported. The context of the peer review was that required by Commission Implementing Regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…E ven through, the potassium carbonate is considered as non-toxic chemical including towards aquatic organisms the present study showed that it can express toxicity to duckweed in 3400 ppm. The same effect was found for potassium hydrogen carbonate which is also considered as low risk chemical towards aquatic plants and algae (Alvarez et al, 2021) and the trials reveal that its toxicity is even lower than potassium carbonate. ANOVA analysis reveal that there were statistically proven differences (p<0.05) in the toxicity toward duckweed between potassium carbonate and potassium hydrogen carbonate.…”
Section: Discussionsupporting
confidence: 62%
“…E ven through, the potassium carbonate is considered as non-toxic chemical including towards aquatic organisms the present study showed that it can express toxicity to duckweed in 3400 ppm. The same effect was found for potassium hydrogen carbonate which is also considered as low risk chemical towards aquatic plants and algae (Alvarez et al, 2021) and the trials reveal that its toxicity is even lower than potassium carbonate. ANOVA analysis reveal that there were statistically proven differences (p<0.05) in the toxicity toward duckweed between potassium carbonate and potassium hydrogen carbonate.…”
Section: Discussionsupporting
confidence: 62%
“…PHC is a naturally occurring inorganic compound that dissociates to potassium ions (K + ) and hydrogen carbonate ions (HCO 3-) in water. Thus, PHC is not considered to be a persistent, bio-accumulative, or toxic compound, and risk assessments performed by EFSA concluded that it poses low risk to soil organisms, among others [48].…”
Section: Discussionmentioning
confidence: 99%